Using Technology to Increase Sales: Influencer Marketing and Viral Marketing - Lestari, Anisa Citra; Tuti, Meylani (Fakultas Seni Rupa dan Desain ITB, 2024)
Companies need to boost sales to draw in clients and influence their purchase decisions at a time when business rivalry is becoming fiercer. As technology develops, many businesses develop new ideas to boost sales through more effective digital marketing, such as viral and influencer marketing tactics. In addition, companies need to use technology strategically to modify their marketing campaigns based on the tastes and actions of their target audience. This study will ascertain how taste, influencers, and viral marketing affect consumer decisions. The people who shop at Roti Keset Condet are the population. An accidental sampling technique yielded a sample size of 250 individuals. With SmartPLS, data analysis employs a structural equation model. The study's findings demonstrate the importance of flavor and viral marketing in influencing consumers' buying decisions. Influencer marketing, however, has no bearing on consumer choices. Consumers who make purchases do so due to viral marketing that is executed, even though the influencer serving as the message's messenger is not the campaign's target. Aside from that, people continue to prioritize taste and image when they are making purchases.